Proceedings of the 19th ACM International Conference on Multimedia 2011
DOI: 10.1145/2072298.2072320
|View full text |Cite
|
Sign up to set email alerts
|

Implicit experiences as a determinant of perceptual quality and aesthetic appreciation

Abstract: Since the Dadaist refusal of the conventional standards in art, followed by Fluxus` rejection of art as a commodity, and recently, the popularity of Internet and technology in art, artworks have become difficult to recognize as artworks in themselves. Modern works of art are no longer readily only seen today, more often fully experienced. The processing of an aesthetic experience needs a new understanding in terms of the changing context of art and the experiential perspective of art recipients. In the multime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Furthermore, correlation between aesthetic ratings and familiarity has been reported in [3]. Content recognizability has been shown to have an influence on aesthetic appeal in [14,17], and abstract paintings were found to be less likely appreciated by people with respect to immediate works of art [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, correlation between aesthetic ratings and familiarity has been reported in [3]. Content recognizability has been shown to have an influence on aesthetic appeal in [14,17], and abstract paintings were found to be less likely appreciated by people with respect to immediate works of art [16].…”
Section: Introductionmentioning
confidence: 99%
“…Along with this quantity, participants also rated the level of recognizability of the content of the image. This second quantity is related to perceptual fluency [17], which is known to have an effect on the aesthetic appeal of works of art. In this study, we wanted to check whether this effect was preserved also when judging the aesthetic appeal of consumer images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may, consequently, influence what viewers consider to be of 'good' or 'bad' quality. Some works (for example [6,21,26,32,33,38]) which do investigate the influence of above-mentioned human factors are often based on subjective tests applied to samples. However, it is seldom the case that samples are deliberately drawn from cross-cultural contexts.…”
Section: Introductionmentioning
confidence: 99%
“…However, an experience of art is more than just the by-products of innate pleasure circuits; there are factors that draw an individual to them. In our previous study we observed that implicit experiences (IE) lead to a positive evaluation of Quality of Experience (QoE) [Mansilla et al, 2011]. On the other hand, it is important to recognize that aesthetic experience is in part modulated by human nature.…”
Section: Introductionmentioning
confidence: 99%